(untitled) (Research, Society and Development, 2025)
This study aimed to identify if the medications used in obstetrics meet the Food and Drug Administration - FDA risk categories. This is an integrative review, in which searches were carried out in the PubMed, SciELO, and Cochrane databases using descriptors. To select publications, the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses - PRISMA were followed. 61 articles were identified, 6 of which were duplicates and were excluded, as well as another 34, discarded after reading the titles and abstracts and 15 after reading in full. Therefore, 6 articles were selected for the study by the proposed objective. In this integrative review, it was observed that pregnant women used different pharmacological classes, so the prescription of potentially harmful medications to pregnant women was not uncommon. Even so, the importance of risk-benefit assessment for the pregnant woman and the fetus, considering that it is possible to face situations in which administering vital treatments for certain chronic conditions may present significant benefits in detriment of the risk.